Cytoskeletal dysregulation and neurodegenerative disease: Formation, monitoring, and inhibition of cofilin-actin rods - Wurz, Anna I.; Schulz, Anna M.; O’Bryant, Collin T.; Sharp, Josephine F.; Hughes, Robert M. (Frontiers in Cellular Neuroscience, 2022)
The presence of atypical cytoskeletal dynamics, structures, and associated morphologies is a common theme uniting numerous diseases and developmental disorders. In particular, cytoskeletal dysregulation is a common cellular feature of Alzheimer’s disease, Parkinson’s disease, and Huntington’s disease. While the numerous activators and inhibitors of dysregulation present complexities for characterizing these elements as byproducts or initiators of the disease state, it is increasingly clear that a better understanding of these anomalies is critical for advancing the state of knowledge and plan of therapeutic attack. In this review, we focus on the hallmarks of cytoskeletal dysregulation that are associated with cofilin-linked actin regulation, with a particular emphasis on the formation, monitoring, and inhibition of cofilin-actin rods. We also review actin-associated proteins other than cofilin with links to cytoskeleton-associated neurodegenerative processes, recognizing that cofilin-actin rods comprise one strand of a vast web of interactions that occur as a result of cytoskeletal dysregulation. Our aim is to present a current perspective on cytoskeletal dysregulation, connecting recent developments in our understanding with emerging strategies for biosensing and biomimicry that will help shape future directions of the field.